Simultaneous determination of calycosin‐7‐O‐β‐d‐glucoside, calycosin, formononetin, astragaloside IV and schisandrin in rat plasma by LC‐MS/MS: application to a pharmacokinetic study after oral administration of Shenqi Wuwei chewable tablets. (21st March 2014) - Sun, Xuehui; Zhang, Pingping; Wu, Xiujun; Wu, Qiong; Zhang, Mengmeng; An, Ye; Shi, Guobing
ABSTRACT A rapid, sensitive and reliable high‐performance liquid chromatography–mass spectrometry (LC‐MS/MS) method was developed and validated for simultaneous quantification of the five main bioactive components, calycosin, calycosin‐7‐O‐β‐d‐glucoside, formononetin, astragaloside IV and schisandrin in rat plasma after oral administration of Shenqi Wuwei chewable tablets. Plasma samples were extracted using solid‐phase extraction separated on a CEC18 column and detected by MS with an electrospray ionization interface in multiple‐reaction monitoring mode. Calibration curves offered linear ranges of two orders of magnitude with r > 0.995. The method had a lower limit of quantitation of 0.1, 0.02, 0.1, 1 and 0.1 ng/mL for calycosin, calycosin‐7‐O‐β‐d‐glucoside, formononetin, astragaloside IV and schisandrin, respectively. Intra‐ and inter‐day precisions (relative standard deviation) for all analytes ranged from 0.97 to 7.63% and from 3.45 to 10.89%, respectively. This method was successfully applied to the pharmacokinetic study of the five compounds in rats after oral administration of Shenqi Wuwei chewable tablets. Copyright © 2014 John Wiley & Sons, Ltd.